PENERAPAN METODE PERMAINAN KOCOK SUMPIT UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VII DI SMPN 1 AIR SALEK - Safitri Ani; Maryamah; Sofyan (STKIP Subang, 2026)
This study was motivated by the low learning motivation of 7th-grade students in the Islamic Religious Education subject at SMPN 1 Air Salek, characterized by a lack of attention, self-confidence, and perceived material relevance, as well as low student learning satisfaction. The study aimed to determine the effect of implementing the